Largely lowered transition temperature of a VO2/carbon hybrid phase change material with high thermal emissivity switching ability and near infrared regulations - Wang, Shancheng (2020)
Vanadium oxide (VO2) as a phase changing material possesses abrupt infrared (IR) transmission and thermal emissivity changing during the metal–insulator transition across transition temperature (τc) of 68 °C. However, the high τc, moderate IR transmission and emissivity regulating ability limits its applications in various fields. A VO2/carbon hybrid phase change material fabricated via homemade plasma enhanced chemical vapor deposition is reported. The material shows a best reported thermal emissivity contrast (0.44) among the experimental values, a largely lowered τc (45 °C), promising a near IR-regulation ability with enhanced photothermal effect in smart windows applications. The theoretical calculation results proved that the improvement of emissivity contrast is due to the hybridization of carbon. This work provides a new approach to synthesize VO2 hybrid materials, which have wide applications in camouflage, sensing, and smart windows.